Analysis of the market drivers of carbon emissions for REITs in Hong Kong, China - Hongyang Li; Wenwei Huang; Lijing Wen; Hongmei Li; Haopeng Yan; Martin Skitmore; Tingting Shi; Xuanying Lai (Journal of Asian Architecture and Building Engineering)
The construction industry is the world’s largest consumers of energy and the largest emitters of greenhouse gases. The potential long-term benefits created by the carbon reduction behaviors of enterprises can be perceived by the market as a means of obtaining a higher premium and economic motivation to implement the carbon reduction strategy. This paper analyzes the correlation between carbon emission performance and the financial performance of Hong Kong real estate investment trusts (REITs) to study the economic incentives for carbon emission reduction actions in the construction industry. The results show that (1) operating margin and Tobin’s Q Ratio are positively correlated with carbon emission performance indicators; (2) the greater the amount of carbon emissions, the better the financial performance − the carbon reduction of related REITs does receive the economic incentive of improving financial performance; (3) the reasons for the lack of carbon emission market drive are the different quality information disclosures of different REITs and the lack of public awareness of carbon emission; and (4) it is necessary to promote the driving force of the REIT carbon emission market through the guidance, incentive, and promotion of government and regulatory agencies and the active participation of micro subjects.